Airway management in a patient with nuchal, interspinous, and flavum ligament rupture by a sickle: a case report. (December 2016) - Sorimachi, Kotaro; Ono, Yuko; Kobayashi, Hideo; Watanabe, Kazuyuki; Shinohara, Kazuaki; Otani, Koji
Abstract Background Penetrating neck injury is an important trauma subset but is relatively rare, especially when involving the posterior cervical column. Rupture of the neck restraints, including the interspinous and flavum ligaments, can create serious cervical instability that requires special consideration when managing the airway. However, no detailed information regarding airway management in patients with profound posterior neck muscle laceration and direct cervical ligament disruption by an edged weapon is yet available in the literature. Case presentation A 63-year-old Japanese man attempted to cut off his head using a sickle after drinking a copious amount of alcohol. On admission, his posterior vertebral column was grossly exposed and the lacerated tissues were actively bleeding, resulting in severe hypovolemic shock. We used a rapid-sequence intubation technique with direct laryngoscopy while manual in-line stabilization of his head and neck was maintained by several people. Surgical exploration revealed nuchal, interspinous, and flavum ligament rupture between his fourth and fifth cervical vertebrae, but no injury to the great vessels was present. The major source of bleeding was a site of oozing from his trapezius and splenius muscles. After surgical hemostasis, wound repair, and subsequent intensive care, our patient was discharged home without any neurological sequelae. Conclusions Deficits of the neck restraints can cause cervical spine subluxation and dislocation secondary to neck movement. Thus, the key to successful airway management in such a scenario is minimization of neck movement to prevent further neurological impairment. We successfully managed an airway using a conventional but trusted endotracheal intubation strategy in a patient with multiple traumas and a suspected spinal cord injury. This case also illustrates that, even when great vessel injury is absent, severe hypovolemic shock may occur after profound neck muscle laceration, requiring immediate surgical intervention.